Freshness/spoilage monitoring of protein-rich foods by betacyanin-loaded gelatin/carboxymethyl cellulose halochromic labels - Reza Abedi-Firoozjah; Shamimeh Azimi-Salim; Arvin Afrah; Reza Yekta; Elham Assadpour; Maryam Azizi-Lalabadi; Seid Mahdi Jafari (Future Foods)
In the present investigation, easy-to-use colorimetric on-package labels were developed based on gelatin/carboxymethyl cellulose films loaded with betacyanin-rich Mirabilis jalapa extract (MJE) for freshness tracking of shrimp and minced meat. The effect of MJE addition (2 %, 4 %, and 6 % (w/v)) on the morphology, micro-structural, optical, and functional characteristics of the labels was assessed. The addition of MJE indicated dose-dependent improvement of antioxidant potential and light barrier capability of the labels but the reduction of their mechanical strength and water barrier properties. The labels underwent color changes (pinkish-red to yellow) after being exposed to different pHs (2–13), which was similar to the MJE solutions when immersed in buffer solutions. The halochromic label loaded with 6 % (w/v) MJE exhibited the highest sensitivity to ammonia. This label was also capable of detecting ammonia concentrations ranging from 0.01 to 0.1 mg/mL, with a visible color shift from red to pale yellow. When utilized for freshness monitoring of shrimp and minced meat, this label displayed noticeable color changes resulting from the accumulation of volatile ammonia and changes in pH during the spoilage of these samples. The labels were also biodegradable, disintegrating within ∼21 days to a great extent. As a result, we found that a label containing 6 % (w/v) MJE can be used as a biodegradable halochromic indicator in the food packaging industry for visual quality monitoring of seafood and meat products.